2019
DOI: 10.1002/uog.20221
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic demonstration of fetal esophagus using three‐dimensional ultrasound imaging

Abstract: Objective To evaluate the feasibility of antenatal direct visualization of normal and abnormal fetal esophagus using three‐dimensional ultrasound (3D‐US) with Crystal Vue rendering technology. Methods Between February and April 2018, 3D‐US volumes were collected from a non‐consecutive series of singleton pregnancies, referred for clinically indicated detailed prenatal ultrasound at 19–28 weeks' gestation to one of two fetal medicine units in Italy. 3D volumes were acquired from a midsagittal section of the fet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Remarkably, in our study, 2 cases in which esophageal atresia was missed in prenatal ultrasound had co-existent esophagotracheal stula, making a correct prenatal diagnosis more challenging. More recently, Dall'Asta et al 25 demonstrated that the detection of esophageal atresia is possible when three-dimensional ultrasound and Crystal Vue rendering techniques are used. Thus, employing the most current ultrasound methods may increase the accuracy of prenatal detection of esophageal atresia.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, in our study, 2 cases in which esophageal atresia was missed in prenatal ultrasound had co-existent esophagotracheal stula, making a correct prenatal diagnosis more challenging. More recently, Dall'Asta et al 25 demonstrated that the detection of esophageal atresia is possible when three-dimensional ultrasound and Crystal Vue rendering techniques are used. Thus, employing the most current ultrasound methods may increase the accuracy of prenatal detection of esophageal atresia.…”
Section: Discussionmentioning
confidence: 99%
“…While 2D ultrasound examination with gray scale and color flow is the stand the antenatal diagnosis of placenta accreta spectrum disorders [22], 3D ultrasoun It is difficult to visualize esophagus on 2D ultrasound examination. The use of 3D ultrasound with multiplanar analysis and Crystal Vue rendering may make the visualization possible [55]. Three-dimensional (3D) volumes are acquired from a midsagittal section of the thorax and upper abdomen with the fetus lying in supine position.…”
Section: D Ultrasound Examination Of Face Limbs and Other Structuresmentioning
confidence: 99%
“…Previous studies that evaluated the feasibility of esophageal visualization during the midtrimester anomaly scan [16][17][18][19] have demonstrated the cervical esophagus in 16%-93% of the cases and the thoracic esophagus in 91.7%-99.5% of the cases. At this stage in pregnancy, due to its length and angled course, the esophagus is demonstrated in segments 17 consequently, a small disruption of the esophagus may be missed.…”
Section: Feasibility Of Esophageal Demonstration Throughout Pregnancymentioning
confidence: 99%
“…It has been previously shown that the normal appearance of the intact esophagus is an uninterrupted echogenic bundle of fibers, visualized as echogenic lines, which is the sonographic signal projected by the collapsed esophageal muscular walls. 17 In order to improve the detection rate of EA several studies have evaluated the feasibility of demonstrating the fetal esophagus throughout pregnancy including during the midtrimester anomaly scan [16][17][18][19] and during the first trimester anomaly scan. 18 The aim of this study was to describe a "one shot" esophageal imaging technique, visualizing the entire esophagus along its longitudinal axis in a single view, and evaluate the feasibility of its use at first and early second trimester.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation